(untitled) (Research, Society and Development, 2022)
Assistive Technology (AT) has been consolidated as a knowledge area in order to provide greater social inclusion, independence and quality of life for people with disabilities and temporary disabilities. This area has an interdisciplinary character, and includes resources and services aimed at promoting the functionality of this population to reduce existing social barriers. To this end, AT needs to be implemented and evaluated based on a change in the medical approach, based on its expanded concept and beyond the resource itself, thus involving the opinion of professionals, as well as the perception of users and family members. Therefore, this study aimed to analyze the scientific productions related to the participation of families in the process of implementing AT resources for children and adolescents. This is an Integrative Literature Review carried out between January and March 2022 using the PubMed and Scielo databases. After performing the search using descriptors from the health area, the researchers selected 07 articles that answered the guiding question. The findings showed a gap in terms of studies that investigate this topic, especially at the national level. Although some articles emphasize the relevance of family-focused practices, these practices are still limited to an informative perspective to be offered to parents, which perpetuates the approach focused on specialists and their knowledge. In this sense, further studies are needed to understand how family members and users can be involved by professionals in therapeutic interventions and in the provision of AT services.